Suicidal Ideation Is Associated With Excessive Smartphone Use Among Chinese College Students - Huang, Qiuping; Lin, Shuhong; Li, Ying; Huang, Shucai; Liao, Zhenjiang; Chen, Xinxin; Shao, Tianli; Li, Yifan; Cai, Yi; Qi, Jing; Shen, Hongxian (Frontiers in Public Health, 2022)
Background: Suicidal ideation is the first step and a strong predictor of suicide. College students are at a considerably high risk of suicidal ideation, and smartphones are commonly used in this group. However, the relationship between suicidal ideation and smartphone use among Chinese college students is unclear. The current study aimed to investigate the prevalence of suicidal ideation among Chinese college students and its association with smartphone use and addiction factors. Methods: A total of four hundred and thirty-nine college students participated the survey. We collected the demographic information, physical health, psychosocial factors (depressive symptoms, social support, sleep quality), characteristics of smartphone use, and mobile phone addiction (MPA). Suicidal ideation was measured with a single question, “did you feel that life was not worth living in the past one year?” Results: The prevalence of suicidal ideation (“Yes” response) in the past year among Chinese college students was 7.5%. In binary logistic regression analysis, suicidal ideation was significantly correlated with less subjective social support (OR:2.49, p = 0.049), lower utilization of social support (OR:13.28, p = 0.012), more depressive symptoms (OR:4.96, p = 0.005), and more than five hours of daily smartphone use (OR:2.60, p = 0.025). Conclusion: Considering the widely use of smartphones in Chinese colleges and the correlation with suicidal ideation, excessive phone use among college students should be given more attention by administrators and health workers. It is necessary to obtain more information about the intention of smartphone use, make full use of smartphones for health education, and monitor excessive use of smartphones, while improving social support and coping mechanisms for depression, to identify suicidal ideation and prevent suicidal behavior among Chinese college students.